1998
DOI: 10.1097/00004424-199808000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Laterality in Parkinson's Disease With Unilateral Symptom by In Vivo 1H Magnetic Resonance Spectroscopy

Abstract: On the basis of NAA/Cr ratios between the symptomatic and the asymptomatic sides, the present 1H MRS study shows a significant neuronal laterality in Parkinson's disease with unilateral symptoms. In vivo 1H MRS may provide a diagnostic marker for neuronal dysfunction in Parkinson's disease with unilateral symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 17 publications
4
37
1
Order By: Relevance
“…Many researchers disclosed a significant reduction of ratios NAA/Cr and NAA/Cho in the temporoparietal cortex [91], the substantia nigra, the basal ganglia [92], the striatum or the occipital lobe [93]. Griffith et al have demonstrated lower NAA/Cr ratios in the posterior cingulate gyrus of demented versus non demented subjects with PD [94].…”
Section: Neurodegenerative Diseases (Alzheimer/parkinson)mentioning
confidence: 99%
“…Many researchers disclosed a significant reduction of ratios NAA/Cr and NAA/Cho in the temporoparietal cortex [91], the substantia nigra, the basal ganglia [92], the striatum or the occipital lobe [93]. Griffith et al have demonstrated lower NAA/Cr ratios in the posterior cingulate gyrus of demented versus non demented subjects with PD [94].…”
Section: Neurodegenerative Diseases (Alzheimer/parkinson)mentioning
confidence: 99%
“…Choe et al. (1998) demonstrated reduced NAA/Cr in PD patients and Holshouser et al. (1995) demonstrated significantly reduced NAA/Cho ratio in PD patients, and researchers have demonstrated that the level of NAA may reflect the status of neuron function.…”
Section: Discussionmentioning
confidence: 95%
“…Abnormal metabolite levels have been demonstrated in motor cortex, 20 presupplementary motor area, 21 temporoparietal cortex, 22 occipital lobe, and lentiform nucleus and striatum. 8,12,15,21,23 Some changes have taken place in association with medications administered for treatment of PD that resulted in increased motor cortex Cho/Cr ratios. 12, 24 Griffith and colleagues, 25 have demonstrated lower NAA/Cr ratios in the posterior cingulate gyrus of demented versus non demented subjects with PD.…”
Section: Discussionmentioning
confidence: 99%